Impact of the MTHFR C677T polymorphism on risk of neural tube defects:case-control study - MOLLOY, ANNE MARIE; SCOTT, JOHN MARTIN (BMJ, 2004)
Homozygosity for the T allele of the C677T polymorphism of the gene encoding the folate dependent enzyme 5,10-methylenetetrahydrofolate reductase (MTHFR) is a risk factor for neural tube defects.1 Both the homozygous (TT) and heterozygous (CT) genotypes are associated with lower tissue concentrations of folate, higher homocysteine concentrations, and lower enzyme activity than the wild type (CC) genotype; these effects are more marked in homozygotes. Low folate and raised homocysteine levels in early pregnancy are risk factors for neural tube defects.2 We investigated the possibility that the CT genotype would also increase the risk of these malformations.
PUBLISHED
Keywords: Clinical Medicine